Liminality Through Eid Al-Adha in High-Density Settlement Kampung Cikini - Nathasya Lintang Ayasha; Evawani Ellisa; Achmad Hery Fuad (Journal of Islamic Architecture, 2026)
This study explores the spatial dynamics of liminality in a densely populated informal settlement in Kampung Cikini, Central Jakarta, during the Eid al-Adha ritual. As in many urban kampungs, in Kampung Cikini, streets and alleys serve as multipurpose spaces where residents extend domestic activities into the public realm, reflecting their adaptability in navigating spatial constraints. The study uses qualitative methods, such as participant observation and interviews, to examine how this unofficial urban setting fosters rituals and social connections. The idea of liminality is used to comprehend how Kampung Cikini's spaces change during Eid al-Adha, demonstrating how small lanes foster intimacy and group ritual attention, thereby fortifying bonds within the community. Streets and alleys, regarded as transitory spaces, can present concerns with mobility ambiguity and environmental sustainability when they become ritual settings. The study suggested that this group's festivity should incorporate eco-friendly customs. The study adds to a larger conversation about the significance of informal spaces in influencing social practices and urban experiences by using the spatial analytic technique of liminality.